(3GdYfa GdeOQSjs - (3UdjHG, RjfIs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3eYgO GdYdhe GdGLJeGYjIs, 2005)
(3JgOa GdOQGSI Edi EdbGA GdVhA Ydi CSHGH GdYfa GdeOQSj hGdJYQa YdjgG, hcTa GdfbGH Yf eXGgQ GdYfa GdJj jeGQSgG GdWdGH Ch Jdc GdJj jJYQVhf dgG aj MjGJge Vef YGFdGJge heOGQSge eY QaGbge hYHQ hSGFd GdEYdGe(B. (3HGdEVGaI Edi JSdjW GdVhA Ydi LGfH egeT aj MjGI gPg GdaFI ef GdWdGH hge aj QjYGf GdYeQ haj eQMdI ObjbI JJchf ajgG TNUjJge hJfHfj ajgG CacGQge habG deG jYjThfg hdeG jJYQVhf dg NdGd gPg GdeQMdI GdYeQjI(B. (3JfGhdJ GdOQGSI eOQSJjf, eOQSI NGUI (B"(3eGQ EdjGS GdMj dQGgHGJ GdYGFdI GdebOSI(B" (3aQY RMdI, heOQSI QSejI (B"(3MhT GdCeQGA(B". (3EYJeOJ Ydi OQGSI GdMGdI, GdedGMXI, hGdESJeGQI GdJj hRYJ Ydi (B111 (3WGdHkG hWGdHI, JfGhdJ GdCSFdI ajgG GdhVY GdELJeGYj ddYGFdI hGdEbJUGOj hGdScfj, hfXGe GdeOQSI hChbGJ GdaQGZ hGdJSdjI, GdEfJQfJ hGdcJH(B. (3JHjf GdfJGFL Cf GdYfa eeGQS OGNd GdeOQSJjf Ydi MO ShGA, EdG Cf CSHGHg JNJda ef eOQSI dCNQi, adOi GdeOQSI GdQSejI jJchf HSHH GdhVY GdEbJUGOj ddCSQI Ch GdfXGe GdUGQe GdeWHb, HGdEVGaI Edi YOe Jage GdeYdejf ddeQMdI GdYeQjI GdObjbI GdJj jeQ HgG GdWGdH hZjGH GdfTGWGJ GdJj JTcd eJfaSkG gGekG def ge aj Sfge(B. (3CeG GdeOQSI GdNGUI jYGfhf WdGHgG ef TNUjI HYV GdeYdejf GdeJSdWI hEfJbGOGJge GddGPYI hJejjRge Hjf GdWdGH, hehGO hSGFd GdEYdGe GdgGHWI JDKQ SdHkG Ydi faSjJge hJRjO EVWQGHGJge hJfYcS Ydi SdhcjGJge aj GdJYGWj eY QaGbge OGNd GdeOQSI(B. (3HGdQZe ef NWhQI eG jJYQV dg GdChdGO aj gPG GdYeQ, JHjf VYa GdhSGFd GdeJhGaQI ddJUOj dgPg GdMGdGJ HTcd QGOY(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Violence; Violence; (3GdYfas